POLITICAL PARTIES AND THEIR ROLE IN SAFEGUARDING THE SUPREMACY OF THE CONSTITUTION - Silvia-Elena, OLARU (Strategii Manageriale, 2014)
Nowadays, the political scene of the world is stirred by political parties. The separate fronts of the Government, on the one side, and Parliament, on the other, are now obsolete notions, while political parties dominate social life, having become genuine states in state. Therefore, within the contemporary organization of the powers in state, the issues are assessed from a different perspective: traditional structures are maintained, while their functions evolve and transform rapidly. A modern society without political parties is unconceivable. Today, more than ever, political parties deserve their qualification of "engines of political life" and "reasons of the aging of the classical theory of the separation of powers"; at the same time, they must act within the boundaries set by law, namely by observing the principles of a democratic state and the constitutional order. When dealing with the theory of the separation of powers in state, we must keep in mind that, to a large extent, it was developed in a time in which political parties did not exist yet or were not in their modern form. The main problems were of institutional nature and referred to the various bodies, their competencies and the relationships between them. Unfortunately, in societies in transition, where authentic democracy is still developing, political parties - in some countries - perceive governing as a means of obtaining ministerial portfolios at all costs, irrespective of whether they have professionals for the field concerned or not. This often creates a governmental crisis, which usually leads to changing the incumbents and obtaining more positions in the new government. In this context, some of the incumbent parties set up all kinds of obstacles in order to limit the number of parties, and if this limitation fails, they manage to create legal provisions which discriminate among parties with seats in Parliament and those which are not represented, both in local and parliamentary elections. However, this is a mistake which has its origins in a misapprehension of the role of political parties in a democratic state, governed by the rule of law, ignoring thus important values such as political and party pluralism.